AN ANALYSIS OF THE ADDRESSES DELIVERED BY THE HEAD OF THE REPUBLIC OF INGUSHETIA YUNUS-BEK EVKUROV BEFORE THE PEOPLE’S ASSEMBLY IN 2010-2017: PROSPECTS OF GROWTH AND OVERCOMING THREATS - ARAPKHANOVA, Leyla (CENTRAL ASIA AND THE CAUCASUS, 2018)
The texts of the Addresses of the Head of the Republic of Ingushetia to the People’s Assembly in 2010-2017 are analyzed. This is the first attempt to examine the policy document from the viewpoint of political science. This document aims to formulate the policy course of the new regional leader and evaluate the successes and shortcomings of his own activities.Special attention is afforded to the complexity of the social, political, and economic situation in the Republic of Ingushetia due to military conflicts in neighboring regions. The tendencies that promoted the consolidation of society and a major shift in its condition are revealed. Comparative analysis allowed for exposing the dominant ideas of these addresses and overcoming the deeply rooted opinion regarding the immutable “instability constant.”The article highlights the main factors that promote the upsurge of crisis events in society. In particular, the implementation of the stabilization policy was undermined by the quickly growing unemployment: in many of the region’s republics with a low level of industrial development, the vast majority of the able-bodied population is unemployed. This situation could have led to a number of problems, such as corruption, crime, etc. The issues of terrorism and kidnapping were of no less significance.Practice revealed that a major breakdown of the stereotype regarding the regional leaders’ inability to deal with the situation only occurred in the Republic of Ingushetia. It was associated with the assumption of office by the new President Yunus-Bek Evkurov in 2008.The new Head of the Republic defined protection of human rights, improvement of the population’s quality of life, a functioning civil society, and a decrease in crime rate as priority issues. A great accomplishment of Evkurov is the overcoming of the crisis and a virtual absence of protest sentiment, explained by a notable growth of prosperity and an improvement in the service sphere, as well as progress in the economic situation as a whole. The policy document, namely, the annual Address of the Head of the Republic of Ingushetia, is used for the analysis of the situation in the region as one of the significant instruments of society’s consolidation. The Address is an element of an open dialog with the people, which allows for publicly addressing the issues and priorities of state policy. Each document’s preamble contains references to the principal facts, achievements, and central events of the current year. The role of federal state institutions in the attainment of the obtained results is mentioned. The President expounds his vision of the strategy of the republic’s socioeconomic development and defines the primary goals for the executive and municipal authorities for the next year.